Interphase nuclear phenotype and chromosomal variation in Cynodon dactylon (L.) pers - Nitu, SK; Islam, SMS; Tarique, H (Journal of Bio-Science, 2019)
Interphase nuclear phenotype in different accessions (Acc.) of Cynodon dactylon studied in the present experiment showed chromocentric nuclear organization and the chromocenters were found to be visible clearly. The chromocenter numbers were not same and sometimes it was found to be significantly less and never more than total number of chromosomes. Percentages of heterochromatin values were expressed per nuclear area and the values range from 19.759% (Acc. 16) to 66.022% (Acc.18). Nuclear volume as well as interphase chromosome volume was found to vary 0.674 μm3 (Acc.6) to 41.921 μm3 (Acc.10) and from 0.028 μm3 (Acc. 6) to 1.905 μm3 (Acc. 10), respectively. The somatic chromosome number found to vary from 12 to 40. 2n = 18 chromosomes were found in eight accessions of C. dactylon. Only one accession was found to be tetraploid and rest of them aneuploid whose chromosome numbers were 12, 14, 16, 22, 24, 26, 32, 40 etc. The availability of aneuploid shows great aspects of forage breeding programme. J. bio-sci. 27: 133-141, 2019